Models of structural design in Danish local government - Klaudi Klausen, Kurt (Politica, 2021)
Danish local governments are using a multitude of governance paradigms, primarily NPM and NPG. It is argued that governance takes the form of packages of design and steering mechanisms that materialize in various models such as the classic bureaucratic organization, the business model, and the corporate model of local government. The historical development of successive packages is explained as attempts to achieve strategic design fit and as isomorphic processes of symbolic adapting. Managers have to be capable of decoding the mix of paradigms, live with the ambiguities and inconsistencies and adapt via strategic maneuvering in order to create meaning and legitimacy.